Gasto tributário e ciclos políticos no Brasil – uma análise para o período de 1998 a 2018 - Sousa Júnior, Ademir Moura de (2019)
The Theory of Political Cycles proposes that governing authorities, knowing the influence that the economic situation has on the vote decision of the voters, interfere in the economic course by manipulating macroeconomic variables and fiscal policy instruments with the goal of votes maximization. In that context, this dissertation has as main goal to analyze empirically if there are evidences of political opportunism in the concession of fiscal benefits implemented by tax exemptions occurred during the governments of the brazilian presidents Fernando Henrique Cardoso, Lula da Silva and Dilma Rousseff. To do so we empirically analyzed tax expenditures in the space of time between 1998 and 2018, relating them to the respective election periods. Ten regressions were estimated for each of the main taxes administered by the Federal Revenue Secretariat, adopting the same functional form for each of them. As a result, only the “Social Contribution on Net Profit” (Contribuição Social Sobre o Lucro Líquido - CSLL) was statistically significant in the direction of the political cycle. It was also observed that there is a very strong correlation between taxes levied on business activity.